Bioengineering from the laboratory to clinical translation in oral and maxillofacial reconstruction - Ola M. Maria; Ashraf Heram; Simon D. Tran (Saudi Dental Journal)
Background: Conventional techniques used in oral and maxillofacial reconstruction focus mainly on utilizing autologous tissues that have unquestionably improved function and esthetics for many patients, worldwide. However, the success depends on countless factors such as: donor and recipient sites conditions, patient’s medical history, surgeon’s experience, restricted availability of high-quality autogenous tissues or stem cells, and increased surgical cost and time. Materials and Methods: Lately, teaming researchers, scientists, surgeons, and engineers, to address these limitations, have allowed tremendous progress in recombinant protein therapy, cell-based therapy, and gene therapy. Results: Over the past few years, biomedical engineering has been evolving from the laboratory to clinical applications, for replacement of damaged body tissues due to trauma, cancer, congenital or acquired disorders. Conclusions: This review provides an outlook on the content, benefits, recent advances, limitations, and future expectations of biomedical engineering for salivary glands, oral mucosa, dental structures, and maxillofacial reconstruction.